The assessment of knowledge management as a fundamental piece of success in companies in southern Peru, 2022 - Fernandez Argandoña, Regis Andre Junior (2022)
This article entitled "The assessment of knowledge management as a fundamental piece of success in companies in southern Peru, in the year 2022"; Its main objective is to determine if the entrepreneur values ??aspects related to knowledge in their organizations and how this management helps to improve the organizational climate of companies through the strengthening of their corporate identity. The type of research was qualitative with a non-experimental design at a correlational level. Regarding the data collection technique and instrument, the interview and the interview guide were used, respectively. Being a qualitative research, it was decided to interview four managers of recognized companies in the city of Tacna. After applying the instrument, it was concluded that companies value and highlight the aspects related to the creation and transmission of knowledge in their organizations, which is why they generate spaces for dialogue, training and grant recognition since they consider knowledge management as a success factor. business by improving the work environment and corporate identity.